The Effect of Economic Gini Ratio, Lecturer Ratio, and Number of Universities Ratio on the Gross Enrollment Rate (Ger) of Higher Education at Indonesia in 2020–2022 - Diani Winarto, Novrissa; Siti Nurjanah; Aditya Pratama (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
Gross Enrollment Rate is a statistical indicator used to measure educational attainment in a country in the form of a percentage. GER HE is a comparison between the number of people still studying at tertiary level regardless of age and the number of people aged 19 - 23 years. The research objective is to determine the effect of the unit in analysis, namely the Economic Gini Ratio, the Ratio of Lecturers, and the Ratio of the Number of Universities on the GER of HEs in Indonesia in 2020 - 2022.  The research method used is a quantitative method with secondary data. The sample used is a saturated sample of an entire population of 102 samples. The technique of data analyzed using regression analysis of data panel. The data panel used is combined time series data from three years, namely 2020 - 2022. Then, data from several objects (cross section) is used, namely data from 34 provinces in Indonesia. Based on the results of the study using the Fixed Effect Model (FEM), it shows that the economic Gini ratio has a negative and significant effect on the GER for higher education institutions by -2.038873 in 2020-2022. Meanwhile, the ratio of lecturers and the ratio of the number of universities have no effect significantly to GER of HEs on 2020-2022 in Indonesia.